La comprensión lectora inferencial de textos especializados y el rendimiento académico de los estudiantes universitarios del primer ciclo - Ugarriza Chávez, Nelly (2006)
The problem of inferential comprehension of specialized texts by students of general studies at a private university (N=717) was the main axis of analysis in this study. The intention was to know the strategies that they used to understand a scientific text. When we analyzed by means of the factorial analysis the cognitive activities they undertook when reading a text of Psychology, we reached a solution of two factors: F1, macro structural processing; and F2 model of the situation. The intervention of the professors was recommended who must promote their approach to the text and teach them adequate strategies for the comprehension of scientific texts of the courses they are in charge.